Polishing Pad

By mixing polyurethane resins A and B of different modulus, the problem that traditional soft polishing pads are difficult to improve the polishing rate and increase the hardness will lead to scratches, achieving the effect of high polishing rate and low scratches.

JP7656465B2Active Publication Date: 2025-04-03FUJIBO HLDG
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2021059336
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-31
Publication Date
2025-04-03
Estimated Expiration
2041-03-31

AI Technical Summary

Technical Problem

Traditional soft polishing pads are difficult to improve the polishing rate due to the weak material, while increasing the hardness to increase the polishing rate will cause scratches on the surface.

Method used

A polishing pad made of mixing polyurethane resins of different modulus is used, specifically, the 100% modulus of polyurethane resins A and B is set to 3-12MPa and 15-40MPa respectively, and mixed in a certain proportion (100:0.1-100:5) to form a polyurethane resin-sheet with multiple crack-shaped bubbles.

Benefits of technology

It effectively suppresses scratches on the polishing surface and improves the polishing rate.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007656465000001
    Figure 0007656465000001
  • Figure 0007656465000002
    Figure 0007656465000002
Patent Text Reader

Abstract

To provide a polishing pad which can suppress occurrence of scratches on a surface of a polished object and has a high polishing rate.SOLUTION: A polishing pad contains a polyurethane sheet which has a plurality of tear-shaped air bubbles and has a polished surface for polishing a polished object, wherein a polyurethane resin constituting the polyurethane sheet contains a mixture of a polyurethane resin A having 100% modulus of 3-12 MPa and a polyurethane resin B having 100% modulus of 15-40 MPa, and a mass ratio of the polyurethane resin A to the polyurethane resin B is 100:0.1 to 100:5.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing pad, and more particularly to a polishing pad for use in CMP of semiconductor devices. [Background technology]

[0002] In order to form multi-layer wiring with precision, the surface of materials such as semiconductor wafers must be flat for each layer. To flatten each layer, a free abrasive polishing method using a polishing pad is usually used. The free abrasive method is a method of polishing the processed surface of an object to be polished while supplying a polishing liquid (polishing slurry) between the polishing pad and the object to be polished.

[0003] Polishing pads for semiconductor device manufacturing require pores on the surface of the polishing pad to hold the polishing slurry, hardness to maintain the flatness of the workpiece, and elasticity to prevent scratches on the workpiece. Polishing pads that meet these requirements have a polishing surface made of urethane resin foam.

[0004] In recent years, Chemical Mechanical Polishing (CMP), a type of free abrasive method, has been used to flatten material surfaces with high precision. CMP is a technique that uses a polishing liquid (slurry) containing abrasives such as silica, anticorrosive agents, surfactants, etc. to modify the surface of the object to be polished while increasing the mechanical polishing effect of the abrasives. In CMP, the polishing liquid containing abrasives penetrates between the object to be polished and the polishing pad, allowing the object to be polished stably while the polishing pad is rotated at high speed.

[0005] Polyurethane resin foam is usually formed by curing through the reaction of a prepolymer containing a urethane bond-containing polyisocyanate compound with a curing agent (dry molding method). Then, this foam is sliced ​​into sheets to form a polishing pad. In this way, a polishing pad with a hard polishing layer produced by dry molding method (hereinafter, sometimes abbreviated as hard polishing pad) has relatively small, roughly spherical bubbles formed inside the foam during polyurethane resin curing molding, so that the polishing surface of the polishing pad formed by slicing has openings (openings) that can hold slurry during polishing processing. When a hard polishing pad is used, the flatness and polishing rate of the substrate can be improved. However, due to its hardness, there is a risk of defects such as scratches occurring. In addition, in recent years, as the width of wiring becomes finer, more precise polishing is required, and there are more and more situations where it is difficult to meet the demands with hard polishing pads. Therefore, polishing pads with soft polishing layers manufactured by a wet film forming method (hereinafter sometimes abbreviated as soft polishing pads) are used, especially in the finishing process. As a soft polishing pad used for the finish polishing in the above-mentioned CMP process, Patent Document 1 discloses a soft suede pad which is less likely to cause micro defects. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] JP 2010-149259 A Summary of the Invention [Problem to be solved by the invention]

[0007] However, since conventional soft polishing pads are made of soft materials, it is difficult to increase the polishing rate, and the polishing rate has been increased by adding fine particles such as carbon black to the soft pad or by increasing the hardness of the resin used in the pad. However, the addition of carbon black or the increase in the hardness of the resin leads to scratches (polishing damage) on the surface of the workpiece to be polished.

[0008] The present invention has been made in consideration of the above problems, and has an object to provide a polishing pad that can suppress the occurrence of scratches on the surface of an object to be polished and has a high polishing rate. [Means for solving the problem]

[0009] As a result of extensive investigations, the present inventors have found that the above object can be achieved by combining polyurethane resins having different 100% moduli, and have thus completed the present invention. That is, the present invention includes the following aspects. [1] A polishing pad comprising a polyurethane sheet having a plurality of teardrop-shaped bubbles and having a polishing surface for polishing an object to be polished, The polyurethane resin constituting the polyurethane sheet contains a mixture of a polyurethane resin A having a 100% modulus of 3 to 12 MPa and a polyurethane resin B having a 100% modulus of 15 to 40 MPa, The polishing pad, wherein the mass ratio of polyurethane resin A to polyurethane resin B is 100:0.1 to 100:5. [2] The polishing pad described in [1], wherein the 100% modulus of polyurethane resin B is at least twice the 100% modulus of polyurethane resin A. [3] The polishing pad according to [1] or [2], wherein the constituent polyol component of the polyurethane resin A is different from the constituent polyol component of the polyurethane resin B. [4] A polishing pad according to any one of [1] to [3], wherein the constituent polyol component of polyurethane resin A contains one polyol component selected from the three types of polyether polyol, polyester polyol, and polycarbonate polyol, and the constituent polyol component of polyurethane resin B contains another polyol component from the three types of polyether polyol, polyester polyol, and polycarbonate polyol, which is different from the one selected as the constituent polyol component of polyurethane resin A. [5] The polishing pad according to any one of [1] to [4], wherein the polyurethane resin B contains a polycarbonate polyol as a constituent polyol component. [6] The polishing pad according to any one of [1] to [5], wherein the polyurethane resin A contains a polyether polyol or a polyester polyol as a constituent polyol component. [7] A polishing pad comprising a polyurethane sheet having a plurality of teardrop-shaped bubbles and having a polishing surface for polishing an object to be polished, the polyurethane resin constituting the polyurethane sheet comprises a mixture of a polyurethane resin A having a 100% modulus of 3 to 12 MPa and a polyurethane resin B having a 100% modulus of 15 to 40 MPa, The mass ratio of the polyurethane resin A to the polyurethane resin B is 100:0.1 to 100:5, The polyurethane resin A contains a polyether polyol or a polyester polyol as a constituent polyol component, and The polishing pad, wherein the polyurethane resin B contains a polycarbonate polyol as a constituent polyol component. [8] The polishing pad according to any one of [1] to [7], wherein the polyurethane sheet does not contain carbon black. [9] A method for producing a polishing pad according to any one of [1] to [8], A step of preparing a resin solution containing a mixture of a polyurethane resin A having a 100% modulus of 3 to 12 MPa and a polyurethane resin B having a 100% modulus of 15 to 40 MPa, wherein the polyurethane resin A and the polyurethane resin B are prepared so that their mass ratio is 100:0.1 to 100:5; A step of applying the resin solution to a film-forming substrate; and A method for manufacturing a polishing pad, comprising the step of immersing the film-forming substrate on which the solution has been applied in a coagulating liquid to coagulate the solution. Effect of the Invention

[0010] According to the present invention, it is possible to obtain a polishing pad that can suppress the occurrence of scratches on the surface of an object to be polished and has a high polishing rate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0011] Hereinafter, an embodiment of the present invention will be described. <<Polishing pad>> The polishing pad of the present invention is a polishing pad comprising a polyurethane sheet having a plurality of teardrop-shaped bubbles and having a polishing surface for polishing an object to be polished, wherein the polyurethane resin constituting the polyurethane sheet comprises a mixture of polyurethane resin A having a 100% modulus of 3 to 12 MPa and polyurethane resin B having a 100% modulus of 15 to 40 MPa, and the mass ratio of polyurethane resin A to polyurethane resin B is 100:0.1 to 100:5.

[0012] <Polyurethane sheet> The polyurethane sheet has a plurality of teardrop-shaped bubbles. The teardrop-shaped bubbles are intended to mean bubbles formed inside the polyurethane sheet by the wet film-forming method (bubbles having anisotropy and a structure in which the diameter increases from the upper part of the resin sheet to the lower part (the side in contact with the substrate)), and are distinguished from approximately spherical bubbles formed by the molding method. Therefore, the polyurethane sheet having a plurality of teardrop-shaped bubbles of the present invention can be said to be a polyurethane sheet formed by the wet film-forming method. The wet film-forming method means a method in which a resin to be formed into a film is dissolved in an organic solvent, the resin solution is applied to a sheet-shaped substrate, and then the organic solvent is replaced by passing the resin through a coagulating liquid in which the organic solvent dissolves but the resin does not dissolve, and the resin is coagulated and dried to form a foam layer. Usually, when a polyurethane sheet is manufactured by the wet film-forming method, the escape route when the organic solvent inside the polyurethane sheet escapes into the coagulating liquid becomes a cavity, and a plurality of approximately teardrop-shaped macro bubbles (teardrop-shaped bubbles) are generated. In the present invention, a polyurethane sheet refers to a sheet having polyurethane resin as the main component (50% by mass or more, preferably 70% by mass or more, more preferably 80% by mass or more, and even more preferably 85% by mass or more), and is clearly distinguished from sheets having other resins (such as silicone resins) as the main component.

[0013] (Polyurethane resin) The polyurethane sheet included in the polishing pad of the present invention contains a polyurethane resin constituting the polyurethane sheet, which comprises a mixture of polyurethane resin A having a 100% modulus of 3 to 12 MPa and polyurethane resin B having a 100% modulus of 15 to 40 MPa. In the present invention, the 100% modulus is an index of the hardness of a resin, and is the value obtained by dividing the load applied when an unfoamed resin sheet is stretched 100% (stretched to twice its original length) by the cross-sectional area. The higher this value, the harder the resin is. The phrase "including a mixture" of resin A and resin B refers to a urethane sheet obtained by forming a film from a mixed resin solution containing resin A and resin B using a wet film-forming method; the above concept does not include a combination sheet obtained by separately preparing a sheet made of resin A and a sheet made of resin B and bonding / laminating them together.

[0014] The 100% modulus of the polyurethane resin A is preferably from 3 to 10 MPa, more preferably from 4 to 10 MPa, and even more preferably from 6 to 9 MPa. The 100% modulus of polyurethane resin B is preferably from 15 to 35 MPa, more preferably from 20 to 30 MPa, and even more preferably from 21 to 27 MPa. The 100% modulus of the polyurethane resin B is preferably at least twice the 100% modulus of the polyurethane resin A, more preferably 2 to 8 times, even more preferably 2 to 6 times, even more preferably 2 to 5 times, even more preferably 2 to 4 times, and even more preferably 3 to 4 times. When the 100% modulus ratio is within the above range, a polyurethane sheet having a phase separation structure is easily obtained, and it is easy to increase the polishing rate while suppressing an increase in the rigidity of the entire polishing pad and suppressing the occurrence of polishing scratches. The 100% modulus can be easily adjusted by adjusting the type and amount of the constituent polyol component and / or the constituent polyisocyanate component. Furthermore, the polyurethane sheet contained in the polishing pad of the present invention preferably has a 100% modulus of the entire resin constituting the polyurethane sheet of 13 MPa or less, more preferably 11 MPa or less, even more preferably 3 to 10 MPa, even more preferably 4 to 10 MPa, and even more preferably 6 to 9 MPa.

[0015] (mass ratio) In the polyurethane sheet contained in the polishing pad of the present invention, the mass ratio of polyurethane resin A to polyurethane resin B is preferably 100:0.1 to 100:5, more preferably 100:0.5 to 100:4, and even more preferably 100:1 to 100:3. When the mass ratio of polyurethane resin A to polyurethane resin B is within the above range, it is easy to increase the polishing rate while suppressing an increase in the rigidity of the entire polishing pad and suppressing the occurrence of polishing scratches.

[0016] (Polyurethane resin) In the polishing pad of the present invention, it is preferable that the constituent polyol component of the polyurethane resin A contained in the resin constituting the polyurethane sheet is different from the constituent polyol component of the polyurethane resin B, and it is more preferable that the constituent polyol component of the polyurethane resin A contains one polyol component selected from the three types of polyether polyol, polyester polyol and polycarbonate polyol, and the constituent polyol component of the polyurethane resin B contains one other polyol component among the three types of polyether polyol, polyester polyol and polycarbonate polyol, which is different from the one selected as the constituent polyol component of the polyurethane resin A. For example, when the polyurethane resin A contains a polyether polyol as a constituent polyol component, it is preferable that the polyurethane resin B contains a polyester polyol or a polycarbonate polyol as a constituent polyol component. Ether bonds, ester bonds, and carbonate bonds each have different properties, and when the polyol type of polyurethane resin A is different from the polyol type of polyurethane resin B, phase separation is likely to occur when polyurethane resin A and polyurethane resin B are used together. If the modulus of polyurethane resin B is high, phase separation with polyurethane resin A will progress further, and the high-modulus, hard resin B will be dispersed due to phase separation, improving strength and allowing a high polishing rate to be obtained. In addition, most of the resin with advanced phase separation is composed of the soft resin A with a low modulus, which also helps to prevent polishing scratches.

[0017] (Polyurethane resin A) Polyurethane resin A has a 100% modulus of 3 to 12 MPa. Polyurethane resin A preferably contains one selected from the three types of polyether polyol, polyester polyol, and polycarbonate polyol as a polyol component constituting the resin (hereinafter referred to as a constituent polyol component), more preferably contains polyether polyol or polyester polyol, and even more preferably contains polyester polyol.

[0018] The polyether polyol is not particularly limited, and various polyether polyols can be used. Examples of preferred polyether polyols include polyethylene glycol (PEG), polypropylene glycol (PPG), polytetramethylene glycol (PTMG), etc. The polyether polyols may be used alone or in combination of two or more.

[0019] The polyester polyol is not particularly limited, and various polyester polyols can be used. Examples of preferred polyester polyols include a reaction product of ethylene glycol and adipic acid, and a reaction product of butylene glycol and adipic acid. The polyester polyols may be used alone or in combination of two or more.

[0020] The polyurethane resin A may or may not contain a polyol other than those mentioned above as a constituent polyol component, but it is preferable that the polyurethane resin A does not contain any polyol.

[0021] (Polyurethane resin B) Polyurethane resin B has a 100% modulus of 15 to 40 MPa. Polyurethane resin B more preferably contains, as a polyol component constituting the resin (constituent polyol component), one type of polyol component other than the one type selected as the constituent polyol component of polyurethane resin A out of three types, polyether polyol, polyester polyol, and polycarbonate polyol, and more preferably contains polycarbonate polyol.

[0022] The polycarbonate polyol is not particularly limited, and various polycarbonate polyols can be used. Examples of preferred polycarbonate polyols include reaction products of diols such as 1,3-propanediol, 1,4-butanediol, 1,6-hexanediol, diethylene glycol, polyethylene glycol, polypropylene glycol, or polytetramethylene glycol (PTMG) with dimethyl carbonate, dialkyl carbonate, diphenyl carbonate, ethylene carbonate, or diethyl carbonate. The polycarbonate polyol may be used alone or in combination of two or more.

[0023] Polyurethane resin B may or may not contain a polyol other than those mentioned above as a constituent polyol component, but it is preferable that it does not contain any polyol.

[0024] Among these, the polishing pad of the present invention is preferably such that the polyurethane resin A contains a polyether polyol or a polyester polyol as a constituent polyol component, and the polyurethane resin B contains a polycarbonate polyol as a constituent polyol, and more preferably such that the polyurethane resin A contains a polyester polyol as a constituent polyol component, and the polyurethane resin B contains a polycarbonate polyol as a constituent polyol. By using the above polyol component, phase separation can be further promoted, and the polishing rate can be further improved. That is, a polyurethane resin having a polycarbonate polyol as a polyol component has low compatibility with a polyurethane resin using a polyether polyol or a polyester polyol due to the high cohesive force of the carbonate group. Here, when the modulus of the polyurethane resin B is sufficiently larger than that of the polyurethane resin A, in addition to the polycarbonate polyol portion having high cohesiveness, the hard segment portion having high polarity increases, so that the polyurethane resin A and the polyurethane resin B are more likely to phase separate, and by using the polyurethane resin A and the polyurethane resin B in combination, a polyurethane sheet with more advanced phase separation can be obtained. The strength is improved by the dispersion of the high modulus, hard resin B due to phase separation, which allows for a high polishing rate. In addition, most of the phase-separated resin is composed of the low modulus, soft resin A, which also helps to prevent polishing scratches.

[0025] (Polyisocyanate component) There are no particular limitations on the polyisocyanate components constituting the urethane resins A and B that constitute the polyurethane sheet, and various polyisocyanate components can be used. Examples of the polyisocyanate component are not particularly limited as long as they have two or more isocyanate groups in the molecule. Examples of the diisocyanate monomer include aromatic diisocyanate monomers such as tolylene diisocyanate (TDI), MDI, xylylene diisocyanate, naphthalene-1,5-diisocyanate, p-phenylene diisocyanate, dibenzyl diisocyanate, diphenyl ether diisocyanate, m-tetramethyl xylylene diisocyanate, and p-tetramethyl xylylene diisocyanate; aromatic triisocyanate monomers such as triphenylmethane triisocyanate; alicyclic diisocyanate monomers such as hydrogenated tolylene diisocyanate, hydrogenated diphenylmethane-4,4'-diisocyanate, hydrogenated xylylene diisocyanate, cyclohexyl-1,4-diisocyanate, and isophorone diisocyanate; and aliphatic diisocyanate monomers such as 1,4-tetramethylene diisocyanate and 1,6-hexamethylene diisocyanate. Two or more of these may be used in combination. Examples of such a polyisocyanate include polyisocyanate components that are normally used in producing polyurethane resins, such as trifunctional or higher polyisocyanurate-type polyisocyanates or biuret-type polyisocyanates, which are modified polyisocyanates based on these diisocyanate monomers.

[0026] (Other resins) The polyurethane sheet contained in the polishing pad of the present invention may contain resins other than polyurethane resin A and polyurethane resin B within the range that does not impair the effects of the present invention, but polyurethane resin A and polyurethane resin B are preferably 50% by mass of the total resin constituting the polyurethane sheet, more preferably 70% by mass or more, even more preferably 80% by mass or more, even more preferably 90% by mass or more, and even more preferably 100% by mass. It is particularly preferable that the resin constituting the polyurethane sheet in the polishing pad of the present invention is a mixture of polyurethane resin A and polyurethane resin B.

[0027] (Other ingredients) The polyurethane sheet may or may not contain inorganic fillers such as carbon black, film forming stabilizers, surfactants, etc. in addition to the above components, as long as the effects of the present invention are not impaired. While inorganic fillers such as carbon black improve the polishing rate, they also cause polishing scratches, so it is preferable for the polyurethane sheet to contain a small amount of inorganic filler, more preferably the amount of inorganic filler is 5 mass % or less (preferably 3 mass % or less, and more preferably 1 mass % or less), and even more preferably it contains no inorganic filler. In addition, it is preferable that the polyurethane sheet contains a small amount of carbon black, and it is more preferable that the amount of carbon black is 5 mass % or less (preferably 3 mass % or less, and more preferably 1 mass % or less), and it is even more preferable that the polyurethane sheet does not contain carbon black.

[0028] (Crystalline phase, amorphous phase, mesophase) In the polishing pad of the present invention, the ratio of the crystalline phase in the polyurethane sheet is preferably 10 to 40% by mass, more preferably 15 to 30% by mass, and even more preferably 20 to 25% by mass. The ratio of the amorphous phase in the polyurethane sheet is preferably 50 to 80% by mass, more preferably 55 to 75% by mass, and even more preferably 60 to 70% by mass. The ratio of the intermediate phase in the polyurethane sheet is preferably 0 to 20% by mass, more preferably 5 to 15% by mass, and even more preferably 10 to 15% by mass. The intermediate phase is a region in which soft segments and hard segments are mixed, and a small fraction of the intermediate phase indicates that the phase separation between the hard segments and the soft segments is clear. If the ratios of the crystalline phase, intermediate phase, and amorphous phase of the polyurethane sheet are within the above ranges, a phase separation structure is easily formed when polyurethane resin A and polyurethane resin B, which has poor compatibility with polyurethane resin A and a high 100% modulus, are added. The content of the crystalline phase was determined by subjecting the polyurethane resin to pulse NMR measurement to determine the ratio of the amorphous phase, mesophase, and crystalline phase.

[0029] (Thickness) There are no particular limitations on the thickness of the polyurethane sheet in the polishing pad of the present invention, but it may be, for example, in the range of 0.3 to 2.0 mm, and preferably 0.6 to 1.2 mm. The thickness can be measured using a shopper-type thickness measuring device (pressure surface: circular with a diameter of 1 cm) in accordance with the Japanese Industrial Standards (JIS K6505). Specifically, the method is as follows. Prepare a sample that is 10 cm square. Place the sample face up on the measuring device. Load 100g / cm 2 The pressure applied to the sample is lowered onto the sample, and the thickness is measured after 5 seconds. Five points are measured per sheet, and the average thickness is taken as the thickness. If a 10 cm square sample cannot be obtained, the average thickness is taken as the thickness.

[0030] (density) The density of the polyurethane sheet is 0.15 to 0.40 g / cm 3is preferable, and 0.20 to 0.30 g / cm 3 When the density is within the above range, a good balance between the polishing rate and scratch resistance is achieved.

[0031] (Compressibility and Compressive Elasticity) In this specification, the compressibility is an index of softness, and the compressive elastic modulus is an index of the ease of return to normal after compressive deformation. The compressibility and compressive elasticity can be determined using a Shopper type thickness gauge (pressure surface: circular with a diameter of 1 cm) in accordance with the Japanese Industrial Standards (JIS L1021). Specifically, the method is as follows. The thickness t0 is measured after applying the initial load for 30 seconds from the no-load state, and then the thickness t1 is measured after applying the final load for 5 minutes from the thickness t0 state. Next, all loads are removed from the thickness t1 state, and the specimen is left for 5 minutes (to be in a no-load state), after which the initial load is again applied for 30 seconds and the thickness t0' is measured. The compression ratio can be calculated using the formula: Compression ratio (%) = 100 × (t0-t1) / t0 (initial load is 100 g / cm 2 , final load is 1120g / cm 2 (It is.) The compressive elastic modulus can be calculated using the formula: Compressive elastic modulus (%) = 100 × (t0'-t1) / (t0-t1) (initial load is 100 g / cm 2 , final load is 1120g / cm 2 (It is.) The compressibility of the polyurethane sheet is preferably 1 to 40%, more preferably 3 to 30%, and even more preferably 5 to 20%. The compressive elasticity of the polyurethane sheet is preferably 70 to 100%, more preferably 80 to 99%, and even more preferably 90 to 98%. When the compressibility and compressive elasticity are within the above ranges, the sheet has excellent conformability to the surface of the workpiece, leading to reduced surface roughness of the workpiece.

[0032] (Shore A hardness) In this specification, the Shore A hardness refers to a value measured in accordance with Japanese Industrial Standards (JIS K7311). In the polishing pad of the present invention, the Shore A hardness of the polyurethane sheet is preferably 5 to 50 degrees (°), more preferably 5 to 40 degrees, even more preferably 10 to 30 degrees, and even more preferably 15 to 25 degrees. When the Shore A hardness of the polyurethane sheet is within the above range, it is easy to achieve both a high polishing rate and low polishing scratches.

[0033] (Average pore diameter) In this specification, the average aperture diameter is an average value of circle-equivalent diameters calculated from the area and number of apertures by binarizing a surface image of a polyurethane sheet. The average pore size of the polyurethane sheet in the polishing pad of the present invention is preferably within the range of 20 to 80 μm, more preferably 25 to 70 μm, even more preferably 30 to 60 μm, even more preferably 30 to 50 μm, and even more preferably 30 to 40 μm. When the average pore size is within the above range, the retention of the slurry is good and a stable polishing rate can be obtained.

[0034] (open area ratio) In this specification, the open area ratio means the ratio (%) of the open area to the surface (polished surface) of the polyurethane sheet. The porosity of the polyurethane sheet in the polishing pad of the present invention is preferably within the range of 5 to 50%, more preferably 10 to 40%, even more preferably 15 to 35%, and even more preferably 20 to 30%. When the opening ratio is within the above range, the retention of the slurry is good, and a stable polishing rate is obtained.

[0035] The polyurethane sheet in the polishing pad of the present invention has a polishing surface for polishing an object to be polished. In the polishing pad of the present invention, the polishing surface of the polyurethane sheet and / or the surface opposite to the polishing surface may be ground (buffed) or not, but it is preferable that the polishing surface of the polyurethane sheet is ground, which results in the presence of many openings originating from microbubbles on the polishing surface, and the polishing rate can be improved by retaining the slurry in the openings. In addition, the polishing pad of the present invention may have grooves, embossing and / or holes (punching) on ​​the polishing surface of the polyurethane sheet. The polishing pad of the present invention may have a light transmitting portion. The polishing pad of the present invention may have a single-layer structure consisting of only a polyurethane sheet, or may have a multi-layer structure in which a substrate is attached to the surface of the polyurethane sheet opposite to the polishing surface. Examples of the substrate include substrates made of nonwoven fabric, PET, and vinyl chloride. There is no particular restriction on the properties of the substrate, but it is preferable that the substrate is harder than the polyurethane sheet (for example, has a higher A hardness or D hardness). By providing a layer harder than the polyurethane sheet, it is possible to suppress the expansion and contraction or bending of the polishing pad when polishing an object to be polished using the polishing pad made of the polyurethane sheet.

[0036] The polishing pad of the present invention can be suitably used for polishing (chemical mechanical polishing (CMP)) and planarizing a workpiece (e.g., a wafer) particularly in the manufacture of semiconductor devices. Examples of materials for the workpiece include silicon, polysilicon, silicon oxide film, silicon nitride, and metals such as Cu, W, Al, Ta, and TiN. The polishing pad of the present invention can suppress the occurrence of scratches on the surface when polishing a workpiece such as a silicon wafer, and can improve the polishing rate.

[0037] (action) The polishing pad of the present invention is capable of suppressing the occurrence of scratches on the surface of the workpiece to be polished and at the same time achieving a high removal rate. The reason for this is not clear, but is presumed to be as follows. In the polishing pad of the present invention, the resin constituting the polyurethane sheet contains a mixture of two types of polyurethane resins with significantly different modulus and cohesiveness, and the proportion of the polyurethane resin with 100% modulus and higher cohesiveness is limited to a low level. This is thought to result in a high polishing rate being achieved by the contribution of the polyurethane resin with high modulus present in places, while the polyurethane resin with lower modulus acts as a base to suppress the occurrence of polishing scratches.

[0038] <Polishing Pad Manufacturing Method> The polishing pad of the present invention may be produced, for example, by the following method for producing a polishing pad of the present invention. The method for producing a polishing pad of the present invention includes the steps of preparing a resin solution containing a mixture of polyurethane resin A having a 100% modulus of 3 to 12 MPa and polyurethane resin B having a 100% modulus of 15 to 40 MPa (wherein polyurethane resin A and polyurethane resin B are prepared so that their mass ratio is 100:0.1 to 100:5), applying the resin solution to a film-forming substrate, and immersing the film-forming substrate to which the solution has been applied in a coagulating liquid to coagulate the solution. Each step will be described below.

[0039] (Process for preparing resin solution) In this step, polyurethane resin A and the above-mentioned polyurethane resin B are dissolved in a water-miscible organic solvent in which these resins are soluble, to prepare a resin solution containing these resins. As the polyurethane resin A and the polyurethane resin B, those described above can be used. Examples of the organic solvent include N,N-dimethylformamide (DMF), methyl ethyl ketone, N,N-dimethylacetamide (DMAc), tetrahydrofuran (THF), dimethyl sulfoxide (DMSO), N-methylpyrrolidone (NMP), acetone, and 1,3-dimethyl-2-imidazolidinone (DMI). The organic solvent may be used alone or in combination of two or more. Among them, the organic solvent is preferably DMF or DMAc. The solid content of the resin solution is not particularly limited, but is preferably 15 to 50 mass%, more preferably 15 to 40 mass%, and even more preferably 20 to 35 mass%. When the solid content is within the above range, the resin solution has a suitable fluidity, and it becomes easy to apply the resin solution uniformly to the film-forming substrate. The resin solution may contain components other than the above components as long as the effects of the present invention are not impaired.

[0040] (Process for applying resin solution to film-forming substrate) The resin solution obtained above is continuously applied to the film-forming substrate so as to be approximately uniform, using a coating machine such as a knife coater, a reverse coater, etc. At this time, the thickness of the coating film can be adjusted by adjusting the gap (clearance) between the film-forming substrate and the die or knife of the coating machine. The film-forming substrate may be any substrate commonly used in the art, without any particular limitations, and examples of the substrate include flexible polymer films such as polyester films and polyolefin films, nonwoven fabrics impregnated with elastic resins, etc. Among these, polyester films are preferably used.

[0041] (Process for solidifying the resin solution) The substrate coated with the resin solution is immersed in a coagulation liquid (coagulation bath) whose main component is water, which is a poor solvent for polyurethane resin, to coagulate and regenerate the polyurethane resin. As the solidification liquid, water, a mixed solvent of water and a polar organic solvent such as DMF, etc., is used. As the polar organic solvent, the water-miscible organic solvent used to dissolve the polyurethane resin, such as DMF, DMAc, THF, DMSO, NMP, acetone, DMI, etc., can be mentioned. The concentration of the polar organic solvent in the mixed solvent is preferably 0 to 20 mass%, more preferably 1 to 20 mass%, and more preferably 5 to 15 mass%. The above-mentioned solidification liquid is preferably water or a mixed solvent of water and DMF, and more preferably a mixed solvent of water and DMF. There are no particular limitations on the temperature of the coagulation liquid or the immersion time, and it is preferable that the temperature be 10 to 60° C., and preferably 15 to 50° C., for example, and that the time be 5 to 120 minutes. In the coagulation liquid, a dense skin layer is first formed at the interface between the applied resin solution and the coagulation liquid. Then, the organic solvent in the resin solution is exchanged with the coagulation liquid through the skin layer, and the polyurethane resin is coagulated and regenerated in a sheet shape on the film-forming substrate, thereby obtaining a resin sheet with the film-forming substrate having a plurality of teardrop-shaped bubbles formed therein.

[0042] Thereafter, the coagulated and regenerated polyurethane sheet is peeled off from the resin sheet, or is washed and dried without being peeled off. The washing treatment removes the organic solvent remaining in the polyurethane sheet. The washing liquid used for washing includes water. After washing, the polyurethane sheet is dried by a conventional method, for example, in a dryer at 80 to 150° C. for about 5 to 60 minutes.

[0043] If necessary, the polished surface and / or the surface opposite to the polished surface of the polyurethane sheet may be ground (buffed). The polished surface of the polyurethane sheet may be grooved, embossed, and / or perforated (punched), and a substrate may be attached to the surface opposite to the polished surface. There is no particular limitation on the method of grinding, and any known method can be used, such as grinding with sandpaper, grinding with a buffing machine or a slicing machine, etc. Among these, the use of a buffing machine or a slicing machine is preferred because it allows a polyurethane sheet with a substantially uniform thickness to be obtained. There is no particular limitation on the shape of the grooves and embossing, and examples thereof include a lattice type, a concentric circle type, a radial type, and the like. When a substrate is attached to a polyurethane sheet to form a multi-layer structure, the layers may be bonded and fixed together, if necessary, under pressure, using double-sided tape, adhesive, etc. There are no particular limitations on the double-sided tape or adhesive used in this case, and any double-sided tape or adhesive known in the art may be selected and used. EXAMPLES

[0044] The present invention will be described in more detail below based on examples, but the present invention is not limited to these examples.

[0045] Example 1 A polyurethane resin-containing solution was obtained by mixing 60 parts by mass of a 30% by mass DMF solution containing a polyester polyurethane resin with a 100% modulus of 7.9 MPa, 3 parts by mass of a 10% by mass DMF solution containing a polycarbonate polyurethane resin with a 100% modulus of 24 MPa, and 35 parts by mass of DMF as a dilution solvent. The 100% modulus of the polycarbonate polyurethane resin is 3.4 times that of the polyester polyurethane resin. The polyester-based polyurethane resin is obtained by reacting a polyester diol obtained by reacting ethylene glycol and propylene glycol with adipic acid, methylenebis(4,1-phenylene)diisocyanate (MDI), and 1,4-butanediol. The polycarbonate polyurethane resin is obtained by reacting MDI with a polycarbonate diol obtained by reacting 1,6-hexanediol with dimethyl carbonate. The polyurethane resin-containing solution was applied to a PET film as a film-forming substrate using a knife coater, and the film was immersed in a coagulating liquid (water) at 18°C ​​for 60 minutes to coagulate and regenerate the polyurethane. The film was then washed and dried, and peeled off from the film-forming substrate to obtain a polyurethane sheet. The surface of the obtained polyurethane foam sheet was ground to a thickness of 0.82 mm. Then, a PET substrate was attached to the surface of the polyurethane sheet opposite to the ground surface using an adhesive, and a part of the polyurethane sheet was embossed with a lattice-shaped mold to obtain a polishing pad.

[0046] Comparative Example 1 A polishing pad having a polyurethane sheet having a thickness of 0.81 mm was obtained in the same manner as in Example 1, except that no polycarbonate polyurethane resin was used, and instead 100 parts by mass of a 30% by mass DMF solution containing a polyester polyurethane resin with a 100% modulus of 7.9 MPa was mixed with 55 parts by mass of DMF as a dilution solvent to obtain a polyurethane resin-containing solution.

[0047] Comparative Example 2 A polishing pad having a polyurethane sheet having a thickness of 0.78 mm was obtained in the same manner as in Comparative Example 1, except that 16 parts by mass of a DMF dispersion containing carbon black and a concentration of 15% by mass was added to the polyurethane resin-containing solution of Comparative Example 1 to obtain a polyurethane resin-containing solution.

[0048] Comparative Example 3 A polishing pad having a polyurethane sheet having a thickness of 0.82 mm was obtained in the same manner as in Example 1, except that 11 parts by mass of a 10% by mass DMF solution containing a polycarbonate-based polyurethane resin having a 100% modulus of 24 MPa was added.

[0049] [Evaluation of physical properties of polishing pads] The thickness, density, compressibility, compressive modulus, Shore A hardness, average pore size, and pore ratio of the polishing layer were calculated by the following methods for the polishing pads of Example 1 and Comparative Examples 1 to 3. The results are shown in Table 2. (1) Thickness of the polishing layer The thickness of the polishing layer obtained in the examples and comparative examples was measured in accordance with JIS K6505 using a dial gauge (minimum scale 0.01 mm) with a load of 100 g / cm 2 The thickness was measured at five points, the center and four corners, of a polishing layer (polyurethane sheet) measuring 10 cm long x 10 cm wide, read to the nearest tenth (0.001 mm), and the average value was taken as the thickness of the polishing layer (mm). (2) Density of the polishing layer A sample piece (10 cm x 10 cm) was cut out from the polishing layer (polyurethane sheet) obtained in the Examples and Comparative Examples, and its mass W0 (g) was measured using an electronic balance (Mettler AJ-180). From the thickness t (cm) measured using a thickness gauge and the mass W0 (g), the bulk density (ρ) was calculated as W0 / t / 100 (g / cm 3 ) was calculated. (3) Compressibility %, Compressive elasticity % The compressibility and compressive modulus were measured using a shopper-type thickness gauge (pressure surface: circular with a diameter of 1 cm) in accordance with JIS L1021. Specifically, the thickness t0 was measured after applying an initial load for 30 seconds from a no-load state, and then the thickness t1 was measured after applying a final pressure for 30 seconds from the thickness t0 state. All loads were removed from the thickness t1 state, and the sample was left for 5 minutes (as a no-load state), after which the thickness t0' was measured again after applying an initial load for 30 seconds. Compression ratio (%) = 100 × (t0-t1) / t0 Compressive elastic modulus (%) = 100 × (t0'-t1) / (t0-t1) Initial load is 100g / cm 2 , final pressure is 1120g / cm 2 . Measurement was performed by. (4) Shore A hardness The Shore A hardness was measured by cutting a polyurethane sheet sample (10 cm x 10 cm) from the polishing pad, stacking a plurality of the sample pieces to a thickness of 4.5 mm or more, and using an A-type hardness tester (Japanese Industrial Standards, JISK7311). (5) Average pore diameter, porosity ratio The average pore size and pore rate were calculated by observing the polished surface of the polyurethane sheet at nine points at 100 times magnification using a scanning electron microscope (JEOL, JMS-5500LV), and then binarizing these images using image processing software (Nikon, ImageAnalyzerV20LABVer.1.3). (6) 100% modulus A non-foamed polyurethane sheet was prepared, and a test piece in the shape of a dumbbell No. 3 was cut out from the sheet. Using this, the tensile stress (MPa) value when the gauge length was elongated to 100% (when elongated to twice the normal length) was measured at a tensile speed of 100 mm / min in accordance with JIS K 6251 (1993).

[0050] [Measurement of the proportion of each segment] The soft segment and hard segment contents of the polished surface of each Example and Comparative Example were determined under the following conditions using pulse NMR measurement. Specifically, a sample piece of about 1 to 3 mm square was cut out from the land part of the polishing pad that had been ground with a cutter, filled in a 10 mmφ sample tube to a height of 1 to 2 cm, and pulse NMR measurement was performed to obtain an attenuation curve. In order to match the obtained attenuation curve with the fitting curve, analysis was performed by the least squares method using a Lorentz function (straight line part) and a Gaussian function (curved part), and the proportion (abundance ratio (%)) of the crystalline phase, intermediate phase, and amorphous phase in the polished surface, as well as the relaxation time (T2) were determined. The fitting and analysis were performed using software attached to the following measurement device. The measurement results are shown in Table 1. (Measurement conditions) Equipment: JNM-MU25, manufactured by JEOL Ltd. Measurement magnetic field strength: 0.58T Observation frequency: 25MHz Observed nucleus: 1H Measurement: Spin-spin relaxation (T2) Measurement method: Solid Echo method Pulse width: 2.2μs Pulse interval: 13.0μs Pulse repetition time: 4.0sec Number of times: 16 Measurement temperature: 20℃

[0051] [Table 1]

[0052] The ratio of the crystalline phase increases mainly due to the fact that the hard segments are aggregated to increase in size and depending on an increase in the amount of the hard segments. The relaxation time of the amorphous phase increases depending on the relative increase in the highly mobile soft segments. As a result of the pulse NMR measurement test, although there is not a large difference in the ratio of the crystalline phase to the amorphous phase between the polishing pad of Example 1 and the polishing pads of Comparative Examples 1 to 3, it can be seen that the relaxation time of the amorphous phase is longer than the others in Example 1, and phase separation is progressing. On the other hand, the relaxation time of Comparative Example 3 is shorter than the others, and it can be seen that it is progressing toward phase mixing.

[0053] (Polishing test) Using the polishing pads of each Example and Comparative Example, 120 silicon wafers with TEOS (tetraethoxysilane) film and 120 silicon wafers with Cu film were polished under the following conditions, and the polishing rate and scratch resistance were evaluated. The evaluation results are shown in Table 2.

[0054] [Polishing conditions] Polishing machine used: Ebara Corporation, product name "F-REX300" Polishing speed (platen rotation speed): 70 rpm Processing pressure: 176g / cm 2 Slurry flow rate: 200mL / min Dresser: 3M diamond dresser, model number "A188" Conditioning: Ex-situ, 30N, 4 scans Polishing time: 60 seconds Polished object: Silicon wafer with TEOS film and silicon wafer with Cu film Polishing slurry: Cabot Corporation, model number "SS-25" diluted 2 times (SS25 original solution: pure water = 1:1 mixture)

[0055] [Polishing rate] The polishing rate (Å / min) was calculated by dividing the thickness measured at each point by the polishing time from the average value of the thickness measured at 121 points for the TEOS film on the wafer before and after the polishing test. The thickness was measured using an optical film thickness and film quality measuring device (KLA Tencor, model number "ASET-F5x" in DBS mode).

[0056] [Evaluation of scratch resistance (presence or absence of polishing scratches)] For the Cu film on the wafer, polishing scratches of 150 nm or more in length were counted on the surface of the Cu part of the wafer after polishing processing of the 13th, 28th, 53rd, 78th, 103rd, and 118th wafers using a surface inspection device (KLA Tencor, Surfscan SP5). If the number of polishing scratches was less than 5, it was evaluated as ○, and if the number was 5 or more, it was evaluated as ×.

[0057] [Table 2]

[0058] <Result> As can be seen from the graph, Example 1, which contains a mixture of two types of polyurethane resins with significantly different 100% modulus, was able to achieve both a high average polishing rate and suppression of polishing scratches. In contrast, the polishing pad of Comparative Example 1, which contains only one type of polyurethane resin with a small 100% modulus, was unable to suppress polishing scratches and had a low average polishing rate. The polishing pad of Comparative Example 2 was able to improve the average polishing rate by adding carbon black to Comparative Example 1, but the polishing scratches were worse than those of Comparative Example 1. The polishing pad of Comparative Example 3, which has a higher proportion of resin B than Example 1, did not achieve sufficient results in either the polishing rate or polishing scratches.

[0059] <Consideration> From the results of the pulse NMR measurements, it can be seen that polyurethane phase separation has progressed in the polishing pad of Example 1. It is believed that by combining two types of polyurethane resins with significantly different 100% modulus, polyurethane phase separation has progressed, making it possible to simultaneously improve the polishing rate and reduce polishing scratches. In contrast, the polishing pad of Comparative Example 1 contains only polyurethane resin A with a small 100% modulus, so the crystalline phase component is the smallest and the amorphous phase component is the largest, and the entire resin is flexible and stretches easily, and the openings on the polishing surface are easily blocked and glazing occurs due to friction with the workpiece during polishing. As a result, it is thought that the slurry and polishing debris do not enter the openings and come into contact with the workpiece, causing scratches. On the other hand, the polishing pad of Comparative Example 3 has a shorter relaxation time for the crystalline phase, amorphous phase, and intermediate phase than the others, and the molecular mobility is limited, so it is thought that phase mixing has progressed. Since the proportion of the added polyurethane resin B is large, the entire resin becomes hard, and scratches are likely to occur due to the increased rigidity of the pad. On the other hand, the polishing pad of Comparative Example 2 had a high removal rate due to the hardness increased by adding carbon black, but it is believed that the hard carbon black particles deteriorated the scratch resistance. [Industrial Applicability]

[0060] The polishing pad of the present invention can suppress the occurrence of scratches on the surface of the workpiece to be polished and has a high polishing rate, and therefore has industrial applicability.

Claims

1. A polishing pad comprising a polyurethane sheet having a plurality of teardrop-shaped bubbles and having a polishing surface for polishing an object to be polished, The polyurethane resin constituting the polyurethane sheet includes a mixture of a polyurethane resin A having a 100% modulus of 3 to 10 MPa and a polyurethane resin B having a 100% modulus of 20 to 30 MPa; and The polishing pad, wherein the mass ratio of the polyurethane resin A to the polyurethane resin B is 100:1 to 100:

3.

2. An abrasive pad as described in claim 1, wherein the polyurethane resin constituting the polyurethane sheet comprises a mixture of polyurethane resin A having a 100% modulus of 6 to 9 MPa and polyurethane resin B having a 100% modulus of 21 to 27 MPa.

3. A polishing pad as described in claim 1 or 2, wherein the mass ratio of polyurethane resin A to polyurethane resin B is 100:1 to 100:1.

7.

4. 4. The polishing pad according to claim 1, wherein the polyurethane resin A and the polyurethane resin B each have a polyol component different from each other.

5. The polishing pad according to any one of claims 1 to 4, wherein the constituent polyol component of the polyurethane resin A comprises one polyol component selected from the three types of polyether polyol, polyester polyol and polycarbonate polyol, and the constituent polyol component of the polyurethane resin B comprises another polyol component different from the one selected as the constituent polyol component of the polyurethane resin A among the three types of polyether polyol, polyester polyol and polycarbonate polyol.

6. 6. The polishing pad according to claim 1, wherein the polyurethane resin B contains a polycarbonate polyol as a constituent polyol component.

7. 7. The polishing pad according to claim 1, wherein the polyurethane resin A contains a polyether polyol or a polyester polyol as a constituent polyol component.

8. A polishing pad comprising a polyurethane sheet having a plurality of teardrop-shaped bubbles and having a polishing surface for polishing an object to be polished, the polyurethane resin constituting the polyurethane sheet comprises a mixture of a polyurethane resin A having a 100% modulus of 3 to 10 MPa and a polyurethane resin B having a 100% modulus of 20 to 30 MPa; The mass ratio of the polyurethane resin A to the polyurethane resin B is 100:1 to 100:3, The polyurethane resin A contains a polyether polyol or a polyester polyol as a constituent polyol component, and The polishing pad, wherein the polyurethane resin B contains a polycarbonate polyol as a constituent polyol component.

9. A polishing pad as described in claim 8, wherein the polyurethane resin constituting the polyurethane sheet comprises a mixture of polyurethane resin A having a 100% modulus of 6 to 9 MPa and polyurethane resin B having a 100% modulus of 21 to 27 MPa.

10. The polishing pad according to claim 8, wherein the mass ratio of the polyurethane resin A to the polyurethane resin B is 100:1 to 100:1.

7.

11. The polishing pad according to any one of claims 1 to 10, wherein the polyurethane sheet does not contain carbon black.

12. A method for producing a polishing pad according to any one of claims 1 to 11, A step of preparing a resin solution containing a mixture of a polyurethane resin A having a 100% modulus of 3 to 10 MPa and a polyurethane resin B having a 100% modulus of 20 to 30 MPa, wherein the polyurethane resin A and the polyurethane resin B are prepared so that their mass ratio is 100:1 to 100:3; A step of applying the resin solution to a film-forming substrate; and A method for manufacturing a polishing pad, comprising the step of immersing the film-forming substrate on which the solution has been applied in a coagulating liquid to coagulate the solution.

Citation Information

Patent Citations

  • Abrasive cloth

    JP2010149259A

  • Polishing pad

    JP2016190313A

  • Polishing pad and method for manufacturing polishing pad

    JP2019084589A